2013
DOI: 10.1021/nn304439f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Geometry and Surface Orientation Influence Mode of Cellular Uptake

Abstract: The overall goal of this project is to determine the uptake patterns of silica nanoparticle geometries in model cells, in order to aid in the identification of the role of geometry on cellular uptake and transport. In our experiments we observed a significant difference in the viability of two phenotypes of primary macrophages; immortalized macrophages exhibited similar patterns. However, both primary and immortalized epithelial cells did not exhibit toxicity profiles. Interestingly uptake of these geometries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
265
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(274 citation statements)
references
References 50 publications
8
265
0
1
Order By: Relevance
“…Far than chemical composition, size and shape are crucial factors determining the relationships between nanoparticles and increasingly complex biological systems (namely from cells to entire organisms) in critical aspects such as organ specificity and biodistribution [36][37][38][39][40], toxicity [41], and cell uptake and fate [39,[42][43][44][45]. Although previously checked in several types of nanostructures, mainly in crystalline nano-and micromaterials, the present study is the first evaluation of form (geometry) and function (cellular uptake) of protein nanoparticle populations.…”
Section: Discussionmentioning
confidence: 99%
“…Far than chemical composition, size and shape are crucial factors determining the relationships between nanoparticles and increasingly complex biological systems (namely from cells to entire organisms) in critical aspects such as organ specificity and biodistribution [36][37][38][39][40], toxicity [41], and cell uptake and fate [39,[42][43][44][45]. Although previously checked in several types of nanostructures, mainly in crystalline nano-and micromaterials, the present study is the first evaluation of form (geometry) and function (cellular uptake) of protein nanoparticle populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that size of IONPs has a significant effect on their in vivo behavior and uptake by cells. Changes in nanoparticle size and shape could lead to alterations in receptor cross-linking and cellular responses [38][39][40]. It is generally agreed that nanoparticles at diameters ranging from 10 to 100 nm are optimal for in vivo applications with acceptable pharmacokinetics.…”
Section: Sizementioning
confidence: 99%
“…InteracƟons with biological systems differ for non-spherical parƟcles, opening up new opƟons for the design of drug delivery systems [1][2][3].…”
Section: Introducɵonmentioning
confidence: 99%
“…ModificaƟon of the geometry changes the Ɵme and mechanism required for uptake [3]. As a consequence, non-spherical parƟcles such as cylindrical parƟcles have the potenƟal to control clearance processes, a core prerequisite for a sustained release system for therapeuƟcs [2,4].…”
Section: Introducɵonmentioning
confidence: 99%